La reparación económica en contra del Estado de acuerdo al artículo 19 de la Ley Orgánica de Garantías Jurisdiccionales y Control Constitucional y su incidencia en la seguridad jurídica y el debido proceso. - Carrera Zurita, Mauricio Javier (2023)
This thesis deals with economic reparation, based on article 19 of the Organic Law of Jurisdictional Guarantees and Constitutional Control. The objective is to establish how the reparation ordered against the state by first-level judges affects legal security and due process against public institutions. The bibliographic research methodology is used. Theoretical information and extensive jurisprudence of the Inter-American Court of Human Rights and the Constitutional Court of Ecuador are collected. As a result of this investigation, it was found that reparation is a concept that many authors date after the Second World War, but this fact is disputed, since at the end of the Second World War the allies made Germany sign the Treaty of Versailles, which imposed, among different geostrategic obligations, the obligation to repair with compensation to the countries affected by their actions in contention. Among the various conclusions reached in this thesis, it is considered that the first level judge is overusing a resource that is not within his jurisdiction and competence.